Paratylenchus sp. associated with pineapple yield decline - Nik Masdek Hassan (2021)
Yield reduction of pineapple on peat soil was recognized as a serious problem since the early 1990s especially on the extensively cultivated commercial farm, but not on the small-size farms. Exploratory studies of the pest and disease incidence and severity conducted on several large commercial farms showed the incidence of bacterial heart rot to average only 3.98%, mealy bug infestation average only 3.97%, number of stunted plants average 7.22% and the number of plants with reddish leaf average 4.33%. Evaluation of the small farms showed that the incidences of bacterial heart rot, mealy bug infestation, number of stunted plants and plants with reddish leaf were also low averaging only 1.13%, 1.74%, 3.37% and 5.5%, respectively. Evaluation of the nematode population from the roots of pineapple from the large commercial farms showed a high population of Paratylenchus sp. and low population of Aphelenchoides sp. and Pratylenchus sp. Root and soil samples taken from the small farms did not show any presence of plant parasitic nematodes. Foliar analysis of the pineapple plants showed the content of potassium in the leaf was low. Detailed studies of the nematode population in the soil and roots of the pineapple plants at various growth stages from several affected commercial farms showed the population of Paratylenchus sp. to be high. The population of other nematodes was low and rarely observed. It is concluded that pineapple yield decline on peat soil was most likely due to the nematode Paratylenchus sp.